Faktor Risiko Pneumonia pada Balita di Indonesia: Narative Review Penelitian Akademik Bidang Kesehatan Masyarakat - Patria, Muhammad Arafat (Universitas Ahmad Dahlan, 2016)
Background: Pneumonia was the cause of death in children under five year in Indonesia, the ranks eighth in the world. Method: This study was narative review study from 14 student’s thesis in public health faculty of Indonesia University 2000-2015. The study aimed to explore the risk factors for pneumonia in children under five in Indonesia. The data collected was analyzed by univariate and bivariate. Results: Most of the thesis already used international literature in the bibliography. All measurement instruments used in the eight thesis did not test the validity and reliability. The risk factors pneumonia are often examined was a toddler and environmental factors. Toddlers breastfeeding factor (mean OR 2.7), immunization (mean OR=7.89) and nutritional status (mean OR 3:57). Environmental factors, existence of the wild-house smoker (mean OR 4.385), the density of homes (mean OR 2:32). Based on t test analysis,there were no differences between the postgraduate and undergraduate final academic paper in the number of independent variables, the reference number, the number of samples and a significant variable. Conclusion: The pneumonia was found commonly in toddlers and environmental factors. The quality of academic writing reviewed were better from year to year.